Women's empowerment through homestead food production in rural Bangladesh - Dupuis, Sarah; Hennink, Monique; Wendt, Amanda; Waid, Jillian; Kalam, Md Abul; Gabrysch, Sabine; Sinharoy, Sheela (BMC public health, 2022)
Women in rural Bangladesh face multiple, inter-related challenges including food insecurity, malnutrition, and low levels of empowerment. We aimed to investigate the pathway towards empowerment experienced by women participating in a three-year nutrition-sensitive homestead food production (HFP) program, which was evaluated through the Food and Agricultural Approaches to Reducing Malnutrition (FAARM) cluster-randomized controlled trial.